Selected properties of hybrid particleboard composite made from oil palm empty fruit bunch (EFB) and Merpauh (IRVINGLA MALAYANAN OLIVE) particles bonded with Melamine urea formaldehyde resin - Hamid, Norul Hisham; Yazid, Mohd Fitri; Hassan, Noraishah; Mokhtar, Mohd. Afiq; Hale, M. D. (International Journal of Development Research, 2015)
The Merpauh (Irvingla malayana olive) sawdust was mixed with empty fruit bunch (EFB) of oil palm tree, aimed to improve the homogeneous EFB particleboard. The EFB and Merpauh fibres with diameter of less than 1 mm and more than 1 mm were prepared and they were mixed with ratios of 40:60, 60:40, 80:20 and 100:0. The particleboard with a target density of 750 Kg/m3 and sized of 340mm x 340mm x 12mm were prepared with 12% melamine urea formaldehyde (MUF) and 3 % hardener. The physical and mechanical properties of particleboard were tested in according to JIS 5908: 2003. The results showed that all the physical and mechanical properties of either mixture (EFB/wood) or homogenous EFB particleboards met a minimum requirement of JIS 5908: 2003 standard, except for thickness swelling.